Nekateri vidiki športnih dejavnosti predšolskih otrok - Videmšek, Mateja (Šport (Ljubljana), 2010)
The characteristics of a pre-school child require a specific and comprehensive approach to be taken by pre-school teachers, sports teachers and other pedagogical staff, which in many ways is different from that applied in adult education. In the preschool period, a child should acquire a broad and varied range of movement experiences which form the basis of subsequent complex movement patterns. This basis must be solid because it significantly influences the child's overall development, their engagement in various sports at a later time and also determines whether sport will become one of the important elements of a person's quality of life in all age periods.
Keywords: motorične sposobnosti; otroški vrtci; predšolski otroci; športna dejavnost; športna vzgoja; športni pedagogi